2003
DOI: 10.2166/wst.2003.0705
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of urban runoff and water quality using remote sensing and artificial intelligence

Abstract: Water quality and quantity of runoff are strongly dependent on the landuse and landcover (LULC) criteria. In this study, we developed a more improved parameter estimation procedure for the environmental model using remote sensing (RS) and artificial intelligence (AI) techniques. Landsat TM multi-band (7bands) and Korea Multi-Purpose Satellite (KOMPSAT) panchromatic data were selected for input data processing. We employed two kinds of artificial intelligence techniques, RBF-NN (radial-basis-function neural net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In addition, the quality and quantity of watershed runoff are strongly dependent on land use and land cover (LULC) and the unit pollutant load applied. Using LULC information, environmental modeling has become much easier in recent years due to the increased availability of a dataset, and the improved ability to manage and visualize geospatial information in geographic Information System (GIS) (Ha, 2003 andPapiri andCiaponi, 2003). Urban hydrology is one of the areas where knowledge, of inevitably both environmental sciences and environmental engineering are necessary when strategies for the optimum solution of environmental problems have to be developed (Allen, et al, 2002 andJurgen, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the quality and quantity of watershed runoff are strongly dependent on land use and land cover (LULC) and the unit pollutant load applied. Using LULC information, environmental modeling has become much easier in recent years due to the increased availability of a dataset, and the improved ability to manage and visualize geospatial information in geographic Information System (GIS) (Ha, 2003 andPapiri andCiaponi, 2003). Urban hydrology is one of the areas where knowledge, of inevitably both environmental sciences and environmental engineering are necessary when strategies for the optimum solution of environmental problems have to be developed (Allen, et al, 2002 andJurgen, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The flood monitoring and damage estimation relied heavily on these curves (Cermak et al, 1979). In another paper, radial-basis-function neural network (RBF-NN) and the ANN artificial intelligence techniques were applied on panchromatic imageries of Landsat thematic mapper (Landsat TM) and Korea multi-purpose satellite (KOMPSAT) in land use/cover classification in an area in Korea (Ha et al, 2003). The outcome was exerted as input for SWMM to predict stormwater runoff quantity and biological oxygen demand (BOD) loading.…”
Section: Gis and Rs Applications In Sewer System Managementmentioning
confidence: 99%
“…Particularly in water quality and quantity modelling, some of the studies demonstrated the use of remote sensing data to retrieve land cover information. For example, Elgy (2001) used airborne data to classify land cover types which was aimed to be used in urban drainage modelling; Thanapura et al (2007) extracted the runoff coefficient from QuickBird and GIS vector layers; water quality models were developed by Ha et al (2003) from Landsat TM multispectral bands and Korea Multi-Purpose Satellite (KOMPSAT) panchromatic data, and Lee et al (2010) from QuickBird satellite imagery.…”
Section: Remote Sensing For Drainage Modellingmentioning
confidence: 99%